2020
DOI: 10.1126/sciadv.aay3314
|View full text |Cite
|
Sign up to set email alerts
|

Slow slip source characterized by lithological and geometric heterogeneity

Abstract: Slow slip events (SSEs) accommodate a significant proportion of tectonic plate motion at subduction zones, yet little is known about the faults that actually host them. The shallow depth (<2 km) of well-documented SSEs at the Hikurangi subduction zone offshore New Zealand offers a unique opportunity to link geophysical imaging of the subduction zone with direct access to incoming material that represents the megathrust fault rocks hosting slow slip. Two recent International Ocean Discovery Program Expeditio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
155
3

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 114 publications
(168 citation statements)
references
References 39 publications
(107 reference statements)
2
155
3
Order By: Relevance
“…Masuda et al (2019) conducted laboratory experiments with quartz and albite and reported that feldspar plays a more dominant role than quartz in limiting the depth extent (thickness) of the seismogenic zone, but the frictional behaviors of other minerals in the lower seismogenic zone still need to be characterized. Frictional behavior depends in part on environmental conditions, including temperature and the presence of water (Blanpied et al 1995;Scholz 1998), and the heterogeneity of fault materials (Barnes et al 2020) or surface morphology (Kirkpatrick et al 2020) at the interface between seismic and aseismic zones also affects seismogenic processes. Therefore, it is important to know the physical properties, especially the frictional properties, of materials in the transition zone around this interface to better understand seismogenic mechanisms.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Masuda et al (2019) conducted laboratory experiments with quartz and albite and reported that feldspar plays a more dominant role than quartz in limiting the depth extent (thickness) of the seismogenic zone, but the frictional behaviors of other minerals in the lower seismogenic zone still need to be characterized. Frictional behavior depends in part on environmental conditions, including temperature and the presence of water (Blanpied et al 1995;Scholz 1998), and the heterogeneity of fault materials (Barnes et al 2020) or surface morphology (Kirkpatrick et al 2020) at the interface between seismic and aseismic zones also affects seismogenic processes. Therefore, it is important to know the physical properties, especially the frictional properties, of materials in the transition zone around this interface to better understand seismogenic mechanisms.…”
Section: Resultsmentioning
confidence: 99%
“…Masuda et al (2019) measured the frictional properties of albite, but those of other plagioclase-series minerals have not yet been measured. In addition, recent investigations of the interface between seismic and aseismic zones have shown that lithological, mechanical, and frictional heterogeneities within the fault zone and the morphology and geometry of the interface significantly affect seismogenic processes (Barnes et al 2020;Kirkpatrick et al 2020). Thus, the material properties of the rocks distributed in the lower part of the seismogenic zone can be expected to critically affect seismogenic processes.…”
Section: Introductionmentioning
confidence: 99%
“…Masuda et al (2019) conducted laboratory experiments with quartz and albite and reported that feldspar plays a more dominant role than quartz in limiting the depth extent (thickness) of the seismogenic zone, but the frictional behavior of other minerals in the lower seismogenic zone still need to be characterized. Frictional behavior depends in part on environmental conditions, including temperature and the presence of water (Blanpied et al 1995;Scholz 1998), and the heterogeneity of fault materials (Barnes et al 2020) or surface morphology (Kirkpatrick et al, 2020) at the interface between seismic and aseismic zones also affects seismogenic processes. Therefore, it is important to know the physical properties, especially the frictional properties, of materials in the transition zone around this interface to understand seismogenic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Masuda et al (2019) conducted laboratory experiments with quartz and albite and reported that feldspar plays a more dominant role than quartz in limiting the depth extent (thickness) of the seismogenic zone, but the frictional behaviors of other minerals in the lower seismogenic zone still need to be characterized. Frictional behavior depends in part on environmental conditions, including temperature and the presence of water (Blanpied et al 1995;Scholz 1998), and the heterogeneity of fault materials (Barnes et al 2020) or surface morphology (Kirkpatrick et al, 2020) at the interface between seismic and aseismic zones also affects seismogenic processes. Therefore, it is important to know the physical properties, especially the frictional properties, of materials in the transition zone around this interface to better understand seismogenic mechanisms.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, seismological observations show a clear correspondence of the lower limit of the seismogenic zone with the 350 to 400 °C isotherm, and this temperature range corresponds better to the transition from brittle deformation to plastic behavior in feldspar than to that in quartz (Hasegawa and Yamamoto 1994). In addition, recent investigations of the interface between seismic and aseismic zones have shown that lithological, mechanical, and frictional heterogeneities within the fault zone and the morphology and geometry of the interface signi cantly affect seismogenic processes (Barnes et al 2020;Kirkpatrick et al 2020). Thus, the material properties of the rocks distributed in the lower part of the seismogenic zone can be expected to critically affect seismogenic processes.…”
Section: Introductionmentioning
confidence: 99%